2009
DOI: 10.1017/s0066477400001908
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Charles Tesoriero, who was born on 2nd July 1973 and died on 21st August 2005, was one of the brightest young stars in the Australasian Classical firmament. A hugely engaging character, with a larger than life personality, he attracted a wide range of people to the study of Latin, which was both his career and his passion. After graduating from the University of Sydney with Honours in Latin, Charles embarked upon his PhD thesis, a commentary on the Erictho episode in Lucan Book 6. During this time he undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The estimation sample is taken from the Household Income and Labour Dynamics in Australia (HILDA) Survey which collects panel data from a nationally-representative sample of more than 7,600 Australian households encompassing almost 20,000 individuals aged 15 and older (see Watson, 2009;Woden et al, 2002). The advantage of HILDA data for our purposes is their detailed information about individuals' demographic and human capital characteristics, occupational classification, hours of work, and labour market earnings.…”
Section: The Estimation Samplementioning
confidence: 99%
“…The estimation sample is taken from the Household Income and Labour Dynamics in Australia (HILDA) Survey which collects panel data from a nationally-representative sample of more than 7,600 Australian households encompassing almost 20,000 individuals aged 15 and older (see Watson, 2009;Woden et al, 2002). The advantage of HILDA data for our purposes is their detailed information about individuals' demographic and human capital characteristics, occupational classification, hours of work, and labour market earnings.…”
Section: The Estimation Samplementioning
confidence: 99%
“…Obervational data, however, suggest that plasma transfusions fail to correct mildly abnormal coagulation tests (Abdel-Wahab 2006;Holland 2006) and are associated with worse clinical outcomes in non-massively bleeding patients (Dara 2005;Karam 2013;Khan 2007;Narick 2012;Sarani 2008;van Stein 2010;Watson 2009). However, these observational studies might suffer from a "confounding by indication" bias, as prognostic factors perceived by the attending physician may influence treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, currently available evidence derived from several retrospective studies in adults suggests that plasma transfusions are associated with increased odds of acute lung injury (Dara 2005;Khan 2007;van Stein 2010), nosocomial infection (Sarani 2008) and transfusion-associated circulatory overload (Narick 2012). In critically ill adults with haemorrhagic shock, a prospective study reported an independent association between plasma transfusions and worse outcomes such as multiple organ failure and acute respiratory distress syndrome (ARDS) (Watson 2009). In critically ill children, a prospective observational study also reported an independent association between plasma transfusions and multiple organ failure and nosocomial infection (Karam 2013).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…The peripheral locations seem attractive to poor households as they can avoid the costs associated with formal and regulated systems of urban land and service delivery. 31 Also another cause of exurban growth leading to ruralopolitan development is the blurred rural-urban distinction, manifested in high population density and improved transport conditions, which makes it increasingly possible for urban elements to be accumulated in situ in rural areas. This is widespread in China.…”
Section: Management Of the Master Planmentioning
confidence: 99%